Spatiotemporal variability from physics to plankton ecology in an upwelling bay - Monique Messié; Mike McCann; Kathleen J. Pitz; Jacoby D. Baker; John P. Ryan; Steven H.D. Haddock; Francisco P. Chavez (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Observing Life in the Sea Using Environmental DNA - Francisco Chavez; Markus Min; Kathleen Pitz; Nathan Truelove; Jacoby Baker; Diana LaScala-Grunewald; Marguerite Blum; Kristine Walz; Charles Nye; Anni Djurhuus; Robert Miller; Kelly Goodwin; et al. (Oceanography, 2021)
The use of environmental DNA (eDNA) for studying the ecology and variability of life in the sea is reviewed here in the context of US interagency Marine Biodiversity Observation Network (MBON) projects. Much of the information in this paper comes from samples collected within US National Marine Sanctuaries. The field of eDNA is relatively new but growing rapidly, and it has the potential to disrupt current paradigms developed on the basis of existing measurement methods. After a general review of the field, we provide specific examples of the type of information that eDNA provides regarding the changing distribution of life in the sea over space (horizontally and vertically) and time. We conclude that eDNA analyses yield results that are similar to those collected using traditional observation methods, are complementary to them, and because of the breadth of information provided, have the potential to improve conservation and management practices. Moreover, through technology development and standardization of methods, eDNA offers a means to scale biological observations globally to a level similar to those currently made for ocean physics and biogeochemistry. This scaling can ultimately result in a far better understanding of global marine biodiversity and contribute to better management and sustainable use of the world ocean. Improved information management systems that track methods and associated metadata, together with international coordination, will be needed to realize a global eDNA observation network.